Analysis of Business Development Strategies in Improving the Economic Welfare of Shrimp Pond Farmers at Gebang District of North Sumatera - Aprilla, Vanya; Harahap, Muhammad Ikhsan; Dharma, Budi (PT Mattawang Mediatama Solution, 2024)
The aim of this research is to examine the shrimp farming industry in Gebang District by analyzing internal and external factors affecting the business, proposing strategies for development, and evaluating the economic welfare of shrimp farmers. Employing a descriptive research methodology with a quantitative approach, data were collected through interviews and questionnaires. Informants were selected using purposive sampling, a non-probability technique, with five informants chosen based on specific criteria. Data analysis utilized the SWOT technique. Findings reveal that the IFAS matrix score is 3.77 and the EFAS matrix score is 4.13. These scores indicate that the shrimp farming industry in Gebang District is best suited to an SO (Growth-Oriented) strategy. This involves optimizing the use of extensive and strategic land to maximize profits, developing and training human resources to enhance farmers' knowledge, and improving facilities and infrastructure to boost production quality and, consequently, selling prices.